Discrete mathematics with ducks - Belcastro, Sarah-Marie (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
"Discrete Mathematics with Ducks is a gentle introduction for students who find the proofs and abstractions of mathematics challenging. At the same time, it provides stimulating material, which instructors can use for more advanced students. The first edition was widely well received with its amusing writing style, and numerous exercises and materials that engaged students at all levels. The new, expanded edition continues to facilitate effective and active learning. It is designed to help students learn about discrete mathematics through problem-based activities. These are created to inspire students to understand mathematics by actively practicing and doing."--
"Serious mathematics treated with levity"--Title page.
"An A.K. Peters book."
"A Chapman & Hall book"--Cover.
Includes bibliographical references (pages 647-648) and index.
Keywords: Mathematics -- Textbooks; Computer science -- Mathematics